2021
DOI: 10.3803/enm.2021.1098
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Nonalcoholic Fatty Liver Disease in Individuals with High Weight Variability

Abstract: Background: Weight loss through lifestyle modification is recommended for patients with nonalcoholic fatty liver disease (NAFLD). Recent studies have suggested that repeated loss and gain of weight is associated with worse health outcomes. This study aimed to examine the association between weight variability and the risk of NAFLD in patients without diabetes.Methods: We examined the health-checkup data of 30,708 participants who had undergone serial examinations between 2010 and 2014. Weight variability was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…NAFLD, which is characterized by fat accumulation in the liver, is a hepatic manifestation of metabolic syndrome (5)(6)(7)(8)(9)(10). Many studies have shown that NAFLD is associated with liver-related morbidity as well as insulin resistance and various metabolic diseases (11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…NAFLD, which is characterized by fat accumulation in the liver, is a hepatic manifestation of metabolic syndrome (5)(6)(7)(8)(9)(10). Many studies have shown that NAFLD is associated with liver-related morbidity as well as insulin resistance and various metabolic diseases (11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…The new lifestyles derived from the lockdown have caused a statistically significant increase in obesity and overweight, which can be quantified with an increase in weight, BMI, percentage of fat mass, and abdominal perimeter as well as alterations in the lipid profile, simultaneously leading to a worsening of the obesity pandemic and an increase in metabolic pathologies [ 41 , 42 ] such as metabolic syndrome, insulin resistance in both the diabetic and non-diabetic individuals, and a greater risk of developing NAFLD [ 43 ], as seen in Table 2 and Table 3 , all of which affect the adult population worldwide [ 44 , 45 ], with metabolic syndrome representing the most frequent chronic liver disease in the United States [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This longitudinal cohort study comprised participants from a Kangbuk Samsung Health Study who underwent comprehensive health examinations annually or biennially at the Kangbuk Samsung Hospital Total Healthcare Centers in Seoul and Suwon, South Korea. In Korea, it is mandatory to participate in regular health check-up programs for every employee and companies to enhance the early detection of disease ( 11 ). For this study, we selected subjects who underwent health checkup, aged ≥18 years, including abdominal ultrasonography and HRV measurements, at least twice between January 1, 2011 and December 31, 2018 ( Supplementary Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%